Pengaruh Tingkat Aktivitas Eksplorasi dan Ukuran Perusahaan Berdasarkan Psak 64 Terhadap Konservatisme Pada Perusahaan Sektor Pertambangan - Warsani Purnama Sari; Yusnaini Yusnaini; Isnaniah Laili Khatmi Safitri; Dhian Rosalina (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2022)
This study aims to determine the effect of the level of exploration activity and company size based on PSAK 64 on conservatism in mining sector companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The population used in this study were 40 mining sector companies listed on the Indonesia Stock Exchange. The sampling method is by using purposive sampling. Based on criteria that have been made the number of samples is 8 companies with an observations are 32 observations. Data processing was carried out using the SPSS 23.0 statistical program. The results of this study indicate that simultaneously, the level of exploration activity and company size based on PSAK 64 have a significant effect on conservatism. Partially, the variable level of exploration activity has no significant effect on conservatism. While the firm size variable has a significant effect on conservatism.